What Makes an Argument Strong? Contrastivism in the New Rhetoric - Scott, Blake D. (Informal Logic)

(untitled) (Informal Logic, 2024)
It is widely believed that Perelman and Olbrechts-Tyteca’s theory of argumentation is vulnerable to the charge of relativism. This paper provides a more charitable interpretation of Perelman and Olbrechts-Tyteca’s normative views, one that properly considers the historical trajectory of their work and a wider range of texts than existing interpretations. It is argued that their views are better characterized as a form of “contrastivism about arguments” than any kind relativism. This more accurate depiction contributes to ongoing efforts to revive interest in Perelman and Olbrechts-Tyteca’s work as well as build bridges with trends in contemporary argumentation theory.